Behavioural economics, travel behaviour and environmental-transport policy. (December 2015) - Garcia-Sierra, Marta; van den Bergh, Jeroen C.J.M.; Miralles-Guasch, Carme
Highlights: Travellers' choices in transport are often best described by behavioural approaches. We present a brief overview of the main insights into behavioural economics. We review empirical evidence on travellers' biased choices. We distinguish between long- and short-term travel choices. Lessons for the design of environmental-transport policies are derived. Abstract: The transport sector creates much environmental pressure. Many current policies aimed at reducing this pressure are not fully effective because the behavioural aspects of travellers are insufficiently recognised. Insights from behavioural economics can contribute to a better understanding of travel behaviour and choices, and the impact of these on policies. Nevertheless, few studies have examined this issue. We review these and provide a broader, more encompassing perspective on environmental policy focused on transport, and taking into account bounded rationality as well as social preferences.